ANALISIS EFISIENSI USAHATANI TEMBAKAU JAWA ASAPAN DI DESA WONOSARI KECAMATAN TRUCUK KABUPATEN KLATEN - Isti Nuryati; Masyhuri Masyhuri; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2006)
This study is purposed to determine : (1) factors that correlates to the production, (2) efficiency, (3) factors that correlates to the technical efficiency evel, (4) factors that correlates to the profit and (%) farms feasibility of smoked Java Tobacco in Wonosari village.This study using basic descriptive method and purposive method for collecting the sample. The smaple are chosen is Wonosari village based on consideration that is the biggest production here and the origin of smoked Java Tobacco cultivation in Klaten Regency. The vollecting of sample to the repondents applied by choosing 0 respondent of secretary, also RT and RW leaders. The collecting of the dta applied by the observation, interview, and noting. Data analysis : for determine actors that influence the production, technical efficiency level and proit, it uses multiple linear regression analysis with Shazam. Professional Edition ; to calculate the allocative fficiency, was done by measuring the ratio between marginal product and input price; to determine the feasibility rate, it uses R/C ratio anlaysis.The analysis result show that the improvement of certain management and technology invention of lan-holding, pesticide and labor, the production can increase and increase rat of fretiizer wioll decrease the production becaused uses fertilizer not efficient yet. The age factor can increase the technical efficiency rating, whereas education and endured family members are not significantly correlates. Factors that has positive and significant correlation to the profit function are; land price, fertilizer price and agriculture moment on August will decrease the profit. Generally, thesmoked Java Tobacco farm’s to practiced and increasing or decreasing input price or ouput price not sensitive to feasibility Smoked Java Tobacco Farms in Wonosari village.